Wheat breeding, productivity and slow variety change: Evidence from the Punjab of India after the Green Revolution - Smale, Melinda; Singh, Joginder; di Falco, Salvatore; Zambrano, Patricia (Wiley, 2008)
Variety change and genetic diversity are important means of combating crop losses from pests and diseases in modern agricultural systems. Since the Green Revolution, genetic diversity among wheat varieties released in India has increased but variety change on farms continues to be slow. In this article, we define and summarise indices of variety change and genetic diversity for the wheat varieties released and grown in Indian Punjab during the post‐Green Revolution period. We evaluate the effect of each index on technical efficiency with a Cobb‐Douglas yield model after testing for exogeneity. Findings support the hypothesis that slow variety change has offset the positive productivity effects of diversifying the genetic base in wheat breeding during the post‐Green Revolution period. Policies that speed the rate of variety change and contribute to a more equitable spatial distribution of modern varieties could support wheat productivity in the Punjab of India, reinforcing plant breeding successes.